Laparoscopic and endoscopic cooperative surgery for gastric cancer mimicking a submucosal tumor - Hiroki Ozawa; Hirofumi Kawakubo; Satoru Matsuda; Shuhei Mayanagi; Tomoyuki Irino; Kazumasa Fukuda; Rieko Nakamura; Norihito Wada; Yuko Kitagawa (Surgical Case Reports)
Abstract Background Gastric cancer that mimics a submucosal tumor (SMT) is infrequently encountered in routine clinical settings, and histopathological analysis is often negative for malignant cells. In such cases, excisional biopsy of the entire tumor may be necessary to make a definitive pathological diagnosis, and laparoscopic and endoscopic cooperative surgery (LECS) is a viable method of excisional biopsy. Case presentation An 80-year-old male patient diagnosed with stomach wall irregularities at routine medical check-up was referred to our facility, and consequent endoscopic examination detected a 20-mm protruded lesion in the greater curvature at the middle third of the stomach. Endoscopic ultrasound (EUS) showed a thick, low echoic lesion with an irregular margin in the second layer of the gastric wall. Further, a nodular part of the lesion had infiltrated into the submucosa, with an appearance similar to that of linitis plastica of the stomach. The lesion was highly suspected to be a gastric carcinoma with submucosal invasion. However, mucosal-incision-assisted biopsy revealed no malignant cells. Computed tomography (CT) identified no metastatic lymph nodes. Therefore, an excisional biopsy using LECS was performed, and to avoid peritoneal dissemination, we used a modified version, namely, combination of laparoscopic and endoscopic approaches to neoplasia with non-exposure technique (CLEAN-NET). The procedure ended without any complications, and post-operative course was uneventful. As histopathology returned a diagnosis of adenocarcinoma pT4a, we performed radical gastrectomy and D2 lymphadenectomy. Post-operative course was unremarkable and the patient underwent follow-up examinations without adjuvant chemotherapy because of old age. Conclusions Local resection using LECS for gastric tumors with a high suspicion of malignancy is useful and feasible. LECS could be used in similar cases.